The Future of Bolsa Familia : An Evaluation of Several Reform Proposals in the Context of Brazil’s Tax Benefit System - Morgandi, Matteo; Do Couto Sousa, Liliana; Farias, Alison; Cereda, Fabio (World Bank, Washington, DC, 2020)
This note aims to contribute to the debate, paying attention not only to changes in the Bolsa Familia program itself, but also by simulating the impact that general spending and tax reforms will have on the well-being of Brazilian families, whether they are poor or not. This last point is particularly relevant in the current fiscal context in which the country is inserted. There is an expenditure ceiling on public accounts that requires cuts in other budget lines in order to implement any expansion in the program. Finally, the note intends to contribute to the debate by elaborating alternatives to the design of the program so that it better meets its function as a social safety net.